2014
DOI: 10.1016/j.fertnstert.2014.03.044
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, pilot trial on the effect of dehydroepiandrosterone on ovarian response markers, ovarian response, and in vitro fertilization outcomes in poor responders

Abstract: HKCTR-1149 (www.hkclinicaltrials.com) and NCT01915186 (www.ClinicalTrials.org).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 43 publications
1
84
2
1
Order By: Relevance
“…6a) [15,17,23]. Six trials including 163 patients that studied women older than 36 also indicated increased oocyte numbers after DHEA treatment (WMD 1.31, [13] Ca se-control None None N/A Intention to treat analysis *** * ** Barad [12] Prospective cohort study None None N/A Intention to treat analysis *** * ** Sonmezer [23] Prospective cohort study None None N/A Intention to treat analysis *** * ** Gleicher [32] Case-control None None N/A Intention to treat analysis *** * ** Wiser [14] RC T Artini [33] RC T Moawad [24] RCT Fusi [25] Prospective cohort study None None N/A Intention to treat analysis *** * ** Hyman [26] Prospective cohort study None None N/A Intention to treat analysis ** * ** Singh [27] Prospective cohort study None None N/A Intention to treat analysis ** * ** Yeung [32] RCT Yilmaz [36] Prospective cohort study None None N/A Intention to treat analysis *** * ** Jirge [15] Prospective cohort study None None N/A Intention to treat analysis *** * ** Kara [28] R C T Vlahos [2] Prospective cohort study None None N/A Intention to treat analysis **** * ** Xu [16] C a s e -control None None N/A Intention to treat analysis ** * ** Yeung [6] R C T Zangmo [17] Prospective cohort study None None N/A Intention to treat analysis ** * ** Zhang [29] RCT Tartagni [30] RCT Tsui [31] Prospective cohort study None None N/A Intention to treat analysis *** * ** Fig. 6b) [12,14,17,25,26,31].…”
Section: Oocyte Numbersmentioning
confidence: 99%
See 2 more Smart Citations
“…6a) [15,17,23]. Six trials including 163 patients that studied women older than 36 also indicated increased oocyte numbers after DHEA treatment (WMD 1.31, [13] Ca se-control None None N/A Intention to treat analysis *** * ** Barad [12] Prospective cohort study None None N/A Intention to treat analysis *** * ** Sonmezer [23] Prospective cohort study None None N/A Intention to treat analysis *** * ** Gleicher [32] Case-control None None N/A Intention to treat analysis *** * ** Wiser [14] RC T Artini [33] RC T Moawad [24] RCT Fusi [25] Prospective cohort study None None N/A Intention to treat analysis *** * ** Hyman [26] Prospective cohort study None None N/A Intention to treat analysis ** * ** Singh [27] Prospective cohort study None None N/A Intention to treat analysis ** * ** Yeung [32] RCT Yilmaz [36] Prospective cohort study None None N/A Intention to treat analysis *** * ** Jirge [15] Prospective cohort study None None N/A Intention to treat analysis *** * ** Kara [28] R C T Vlahos [2] Prospective cohort study None None N/A Intention to treat analysis **** * ** Xu [16] C a s e -control None None N/A Intention to treat analysis ** * ** Yeung [6] R C T Zangmo [17] Prospective cohort study None None N/A Intention to treat analysis ** * ** Zhang [29] RCT Tartagni [30] RCT Tsui [31] Prospective cohort study None None N/A Intention to treat analysis *** * ** Fig. 6b) [12,14,17,25,26,31].…”
Section: Oocyte Numbersmentioning
confidence: 99%
“…However, the outcomes of these treatments have been less than satisfactory [1,5]. Dehydroepiandrosterone (DHEA) is an endogenous steroid produced in the zona reticularis of the adrenal cortex and by ovarian theca cells [6]. In the ovary, it promotes follicular development and granulosa cell proliferation by increasing intraovarian androgen concentrations [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S., another problem is that, Congress legislatively prohibits funding of all IVF-related research, and there is lack of interest by the pharmaceutical industry to support such research. As a consequence, so far, therefore, only two small, greatly underpowered clinical trials of DHEA have been published in women with LFOR (Wiser et al 2010, Yeung et al 2014.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…We have recently performed a meta-analysis examining this question and of 22 studies available at the time, only 3 controlled studies were eligible for analysis, which showed no benefit of DHEA supplementation on clinical pregnancy or miscarriage rates (30). More recently a few small randomised controlled studies, albeit having some methodological weaknesses, have similarly reported that DHEA does not improve clinical outcome in women with diminished ovarian reserve undergoing IVF treatment (31)(32)(33)(34) although it is significant that only one of these studies was placebo-controlled and even then the size of this RCT was very small with 16 participants per treatment arm (31).…”
Section: Introductionmentioning
confidence: 99%